(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Code switching, the alternation between two or more languages or dialects within a single communicative event, is a widespread phenomenon in multilingual societies. This paper examines the theoretical underpinnings, social functions, and implications of code switching, drawing on prior studies to analyze its role in identity construction, pragmatic communication, and linguistic adaptability. Through a review of key frameworks—such as Poplack’s equivalence constraint and Gumperz’s contextualization cues—the study highlights how code switching operates as both a linguistic strategy and a sociocultural marker. Findings suggest that code switching is not merely a byproduct of language contact but a deliberate act of agency that reflects individual and collective identities in diverse global contexts. The paper concludes with implications for education, language policy, and future research in sociolinguistics.